2016
DOI: 10.4269/ajtmh.16-0268
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Plasmodium vivax Malaria in Peru

Abstract: Malaria in Peru, dominated by Plasmodium vivax, remains a public health problem. The 1990s saw newly epidemic malaria emerge, primarily in the Loreto Department in the Amazon region, including areas near to Iquitos, the capital city, but sporadic malaria transmission also occurred in the 1990s–2000s in both north-coastal Peru and the gold mining regions of southeastern Peru. Although a Global Fund-supported intervention (PAMAFRO, 2005–2010) was temporally associated with a decrease of malaria transmission, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 76 publications
1
81
0
1
Order By: Relevance
“…In Colombia, 89.3% of malaria cases originated from the six regions with the highest gold mining activity [5,35]. In Peru, until 2015, health facilities located in areas of intense illegal gold mining (Madre de Dios region) reported 30 times more malaria cases than those in non-mining areas [13,36]. This region, in which gold mining is the main economic activity, had the third largest number of malaria cases in Peru despite being the least populated area [13].…”
Section: State-level Data From Surveillance Systemsmentioning
confidence: 99%
“…In Colombia, 89.3% of malaria cases originated from the six regions with the highest gold mining activity [5,35]. In Peru, until 2015, health facilities located in areas of intense illegal gold mining (Madre de Dios region) reported 30 times more malaria cases than those in non-mining areas [13,36]. This region, in which gold mining is the main economic activity, had the third largest number of malaria cases in Peru despite being the least populated area [13].…”
Section: State-level Data From Surveillance Systemsmentioning
confidence: 99%
“…The most recent WHO data showed that Peru reported an estimated 14.3% of all malaria cases in the region for 2016; this amounted to 56,606 cases, of which 73% were P. vivax [1]. This estimate has been rising fairly steadily since 2010-2011, ever since cessation of the international financial support provided by the Global Fund Malaria Project "PAMFRO" that had successfully reduced the annual incidence to <1 case/1000 inhabitants for 2010 and 2011 [62]. After 2011, there was a surprisingly rapid malaria resurgence, hypothesized to be due to: (1) budgetary constraints; (2) the perception that malaria was under control; and (3) a concurrent regional dengue epidemic in Loreto [63].…”
Section: Perumentioning
confidence: 99%
“…After 2011, there was a surprisingly rapid malaria resurgence, hypothesized to be due to: (1) budgetary constraints; (2) the perception that malaria was under control; and (3) a concurrent regional dengue epidemic in Loreto [63]. Transmission may have been worsened due to the historic Loreto flood of 2011-2012 that inundated and damaged many riverine communities [62]. During the period between 2002 and 2013, 79% of cases were P. vivax and 21% P. falciparum [11].…”
Section: Perumentioning
confidence: 99%
“…In the Peruvian North Coast (PNC), the number of P. vivax malaria cases increased significantly between 2007 and 2010; from 1,733 (4%) to 3,922 (15%) despite a significant decline in the total number of cases from 43,467 to 26,878 in all of Peru. 3 On the other hand, neighboring countries such as Ecuador reported a sustainable decrease in P. vivax cases since 2001 (106,641) through 2012 (558). This reduction in P. vivax cases was supported by economic growth and malaria control efforts by international organizations such as the Malaria Control in Border Zones of the Andean Region Program (PAMAFRO), Amazon Malaria Initiative of the United States Agency for International Development, and the Roll Back Malaria of the World Health Organization/Pan American Health Organization.…”
Section: Introductionmentioning
confidence: 99%